Abundance of the bearded fireworm Hermodice carunculata (Polychaeta: Amphinomidae) increases across a euphotic-mesophotic depth gradient in the remote St. Peter and St. Paul’s Archipelago - Marcos Rogerio Rosa; Erika Flávia Crispim de Santana; Gabriel Malta De Farias; Paulo Yukio Gomes Sumida; Ronaldo Bastos Francini Filho (Ocean and Coastal Research)
The bearded fireworm Hermodice carunculata is widely distributed across tropical and subtropical Atlantic and Mediterranean Oceans and was previously considered to be mostly associated with shallow reefs. We provide here data on the distribution, abundance and habitat use of H. carunculata across a euphotic-mesophotic gradient (0-90 m) in the Saint Peter and Saint Paul’s Archipelago (SPSPA, Mid Atlantic Ridge, Brazil). Samples were obtained using SCUBA and a Remote Operated Vehicle (ROV). A total of 189 individuals were observed and a sharp increase in abundance with depth was recorded, particularly from 50 m depth onwards. In the mesophotic zone (50-90 m) individuals were closely associated with branching black-corals (Tanacetipathes spp.) and predation over black-corals and the scleractinian Madracis decactis was commonly sighted. A Boosted Regression Tree model indicated black-coral abundance as the main driver of H. carunculata abundance, suggesting that preference for optimal habitats to hide/forage is more important than depth per se on the bathymetric distribution of the fireworm. The high abundances of H. carunculata in the mesophotic zone, and its predation on keystone benthic cnidarians, suggests that this species play important roles in the dynamics of deep reefs.